2010
DOI: 10.1071/rd09312
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oocyte vitrification on histone modifications

Abstract: Vitrification has been widely used as an assisted reproductive technology in animals and humans, yet the impact of oocyte vitrification and warming on survival and histone modifications has to be evaluated. In the present study, the survival of mouse MII oocytes was assessed after freezing, as were changes in histone 3 lysine 9 (H3K9) dimethylation, histone 4 lysine 5 (H4K5) acetylation and histone 3 lysine 14 (H3K14) acetylation. The results show that, in oocytes subjected to vitrification, H3K9 methylation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…In contrast, vitrification has been found to reduce gene methylation in mouse oocytes [113], embryos [112], and fetuses [117]. However, other studies have demonstrated that vitrification significantly increases gene methylation in mouse oocytes [116] as well as bovine two cell embryos and the resulting in vitro-derived blastocysts [111]. Regarding the effects of vitrification on acetylation patterns, several studies have indicated that vitrification significantly alters acetylation patterns in oocytes [92,114,116,118,120].…”
Section: Molecular Effects Of Cryopreservationmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, vitrification has been found to reduce gene methylation in mouse oocytes [113], embryos [112], and fetuses [117]. However, other studies have demonstrated that vitrification significantly increases gene methylation in mouse oocytes [116] as well as bovine two cell embryos and the resulting in vitro-derived blastocysts [111]. Regarding the effects of vitrification on acetylation patterns, several studies have indicated that vitrification significantly alters acetylation patterns in oocytes [92,114,116,118,120].…”
Section: Molecular Effects Of Cryopreservationmentioning
confidence: 87%
“…However, other studies have demonstrated that vitrification significantly increases gene methylation in mouse oocytes [116] as well as bovine two cell embryos and the resulting in vitro-derived blastocysts [111]. Regarding the effects of vitrification on acetylation patterns, several studies have indicated that vitrification significantly alters acetylation patterns in oocytes [92,114,116,118,120]. The conclusions of these studies are somewhat contradictory, suggesting that the effects of vitrification on gene methylation patterns vary in a manner dependent on species, developmental stage, and genes, and may also depend on the size of the analyzed genomic regions [110].…”
Section: Molecular Effects Of Cryopreservationmentioning
confidence: 96%
“…Environmental factors can also alter the pattern of histone modification in oocytes. For example, vitrification followed by thawing of oocytes has been show to increase dimethylation of lysine-9 of histone-3 (H3K9) as well as acetylation of lysine-5 of histone-4 (H4K5) (17).…”
mentioning
confidence: 99%
“…Vitrification significantly increased the putative ICR methylation level of H19 in bovine two-cell embryos (71.4% AE 5.7% vs. 60.7% AE 3.5%), which was similar to the H3K9 methylation level found in vitrified mouse oocytes (18). These experiments demonstrated that vitrification significantly increased the methylation level in vitrified embryos or oocytes after immediate warming.…”
Section: Effect Of Vitrification On the Putative Icr Methylation Levementioning
confidence: 62%
“…Researchers have investigated the effect of cryopreservation on DNA methylation in mammalian oocytes (7,(18)(19)(20), embryos (6), and oocytes from cryopreserved ovaries (21), and obtained conflicting results. In addition, no effective methods to positively regulate DNA methylation changes that occur during vitrification have been reported.…”
mentioning
confidence: 98%